regime preventivo e repressivo cabo-verdiano - Monteiro, Gracelino Mendes Varela (2016)
As it´s known, with the elimination of physical boundaries and the advancement of technologies of information and communication, many companies that carry out lawful activities had their activities expanded. On the other hand, many criminal companies whose purpose is to expand their criminal activities (organized crime) have also emerged, in which their main livelihood is the legitimization of crime products. Thus, as a result of this situation, in the 80s, many international organizations have begun to fight money laundering, due to the severity and development of this crime. Initially, it was with the 1988 Vienna Convention, Subsequently other international, supranational and regional organizations also began to fight the crime mentioned above. At the beginning, the only underlying laundering crime was drug trafficking. Then, several states have begun to show some concern with the above situation and ended up creating legislation to combat money laundering. Cape Verde was not exception and eventually regulate money laundering for the first time in drug law, law number 78 / IV / 93 of July 12th. The crime of money laundering is the concealment of proceeds of crime in order to prevent its confiscation and its detection by the State. It is considered a serious crime and undermines the achievement of justice. Still, jeopardizes the proper functioning of competition among firms and weakens the intuitions of the state of democratic right, pinching, thus the international image of a state. In Cape Verde, despite of having followed all the guidelines of combat at legislative levels, there have been only two convictions for the crime of money laundering so far. Thus, one is left with the conviction that this is a symbolic criminal law - when a state due to pressure from the media, international communities and citizens, creates an ineffective criminal type, whose purpose is to win votes with the violation of the classical principles of criminal law.Como é sabido, com a eliminação das fronteiras físicas e o avanço das tecnologias de comunicação e de informação, muitas empresas que exercem as suas actividades de formas lícitas expandiram as suas actividades. Por outro lado, surgiram também muitas empresas do crime, cuja finalidade é expandir as suas actividades criminosas (crime organizado), em que a legitimação dos produtos do crime constitui o seu principal sustento. Assim, como fruto desta situação, na década de 80, devido à gravidade e ao desenvolvimento deste crime, muitas organizações internacionais começaram a lutar contra o branqueamento de capitais. Inicialmente, foi com a Convenção de Viena de 1988. Posteriormente, outras organizações de caris internacionais, supranacionais e regionais começaram também a lutar contra o crime atrás mencionado. No início, o único crime subjacente ao branqueamento era o tráfico de droga. Depois, vários Estados começaram a mostrar alguma inquietação com a situação acima descrita e acabaram por criar a legislação de combate ao branqueamento. Cabo Verde não fugiu à regra e acabou por regular o branqueamento de capitais pela primeira vez na lei de droga, lei nº. 78/IV/93, de 12 de Julho. O crime de branqueamento de capitais consiste na dissimulação dos produtos do crime, com a finalidade de impedir o seu confisco e a sua detecção por parte do Estado. É considerado um crime grave e lesa a realização da justiça. Ainda, põe em perigo o bom funcionamento da concorrência entre as empresas e fragiliza as intuições do estado do direito democrático, beliscando, deste modo, a imagem internacional de um Estado. Em Cabo Verde, apesar de se ter seguido todas as orientações de combate aos níveis legislativos, até a data só houve duas condenações pelo crime de lavagem de capitais. Deste modo, fica-se com a convicção de que estamos perante um direito penal simbólico - quando um Estado, devido às pressões da comunicação social, comunidades internacionais e dos cidadãos, cria um tipo penal ineficaz, cuja finalidade é de ganhar votos, com a violação dos princípios clássicos do Direito Penal